Special anti-cracking cement for marine concrete and preparation method of special anti-cracking cement
By using nano-silica fume, drift beads and masterbatch in offshore concrete, the crack-resistant cement prepared by using nano-silica fume, drift beads and masterbatches, the problems of early cracking and erosion resistance of offshore concrete are solved, and the effect of improving the compressive strength and durability of concrete is achieved.
Patent Information
- Application Number
- CN202510100647.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
AI Technical Summary
Offshore concrete is prone to early cracking problems in service environments, resulting in performance deterioration and structural safety hazards. It is difficult for the existing technology to effectively solve this problem.
The concrete powder anti-cracking agent prepared from nano-silica fume, drift beads and masterbatch is used to prepare crack-resistant cement for offshore concrete in cement formula. The chloride ions in seawater are cured through the hydration process of crack-resistant cement to reduce concrete erosion.
Effectively inhibit the shrinkage and cracking of marine concrete, avoid cracks, reduce ions erosion on concrete, improve the compressive strength and durability of concrete, and do not contaminate seawater.
Smart Images

Figure BDA0005254102810000031 
Figure BDA0005254102810000051 
Figure BDA0005254102810000052
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic building materials and relates to a special anti-cracking cement for marine engineering concrete and a preparation method thereof. Background Art
[0002] Since the 21st century, my country's construction has entered a stage of rapid development. The scale of major infrastructure projects has been unprecedented, urbanization has developed rapidly, and various super-high, super-long and super-large structures have continued to emerge, which has put forward new and higher requirements for the strength, fluidity and durability of special concrete.
[0003] Modern concrete, characterized by the widespread use of various chemical admixtures and industrial by-products, has reduced resource consumption, reduced material carbon emissions, met the performance requirements of modern civil engineering design and construction, and provided strong support for the vigorous development of infrastructure construction. However, engineering practice has found that the problem of early cracking of concrete structures has become increasingly prominent, and the resulting accelerated rate of concrete performance degradation has buried huge hidden dangers to the long-term durability and service life of the structure, especially in marine concrete. The service environment of marine concrete structures is complex and diverse, and the generation of cracks poses a great threat to the durability and structural safety of concrete, especially when marine concrete is corroded by chloride ions and sulfate ions, and the risk of cracking is greater.
[0004] At present, the problems of cracking and corrosion resistance of marine concrete structures are solved by adding additional expansion admixtures to the concrete mix to inhibit cracking of concrete and corrosion of chloride ions and sulfate ions; on the other hand, anti-corrosion admixtures are added to the concrete to reduce the degree of corrosion of chloride ions and sulfate ions; and cement-based anti-seepage materials are sprayed on the concrete surface. However, the use of concrete expansion admixtures or anti-corrosion admixtures is cumbersome to produce and operate, and requires an additional raw material and metering equipment. In addition, the admixture dosage is low, and it is difficult to mix evenly in a short time, making it difficult for the expansion admixture and anti-corrosion admixture to function. On the other hand, the chloride concentration in seawater is different, and the amount of admixture required in different environments is difficult to grasp. Too much or too little will affect the effect of the admixture, and the anti-corrosion problem of marine concrete cannot be fundamentally solved; and spraying cement-based curing agents on building structures can only inhibit the early microcracks below 0.2μm from expanding, and it is difficult to effectively control large cracks, and can only serve as an auxiliary role; in addition, the addition of expansion admixtures or anti-corrosion admixtures and spray curing agents will seep out of the concrete surface and pollute the marine environment. Summary of the invention
[0005] In view of the characteristics of marine engineering concrete, the present invention provides a special anti-cracking cement for marine engineering concrete and a preparation method thereof. The present invention adds a concrete powder anti-cracking agent prepared from nano silica fume, floating beads and masterbatch to the cement formula to prepare a special anti-cracking cement for marine engineering concrete. The present invention prepares a special anti-cracking cement for concrete from the source. The anti-cracking cement is used to prepare marine engineering concrete. On the one hand, it can inhibit the shrinkage cracking problem of large-volume marine engineering concrete, avoid the generation of cracks, avoid ions from entering the concrete, and reduce the erosion of ions on the internal concrete. On the other hand, the anti-cracking cement can solidify the chloride ions in the seawater during the hydration process, reducing the degree of erosion of the concrete. Furthermore, the capillary structure of the anti-cracking cement in the hydrated dense concrete will not pollute the seawater and affect marine life. Therefore, it is used to prepare marine engineering concrete, and there is no need to add any additional anti-cracking and anti-corrosion admixtures to the concrete ratio, which can solve the cracking and anti-corrosion problems of marine engineering concrete.
[0006] The technical solution of the present invention is: a special anti-cracking cement for marine engineering concrete, characterized in that its components and weight ratio are: cement clinker 73-78%, desulfurized gypsum 4-6%, mineral powder 6-8%, fly ash 6-8%, concrete powder anti-cracking agent 4-5%.
[0007] The physical indexes of the anti-cracking cement of the present invention refer to the indexes of PO42.5 cement, with a 3d strength of 25-27Mpa, a 28d strength of 53-55Mpa, and a 45μm sieve residue of 6.0±1%.
[0008] The components and weight ratio of the above concrete powder anti-cracking agent are: 20-30% nano silica fume, 20-30% floating beads, and 40-60% masterbatch. The preferred ratio is: 25% nano silica fume, 25% floating beads, and 50% masterbatch, wherein the components and weight ratio of the masterbatch are: 50-60% concrete stabilizer, 10-15% complexing agent, 10-15% defoaming agent, and 10-20% penetrant.
[0009] The complexing agent is one or two of diethylenetriaminepentaacetic acid and trisodium hydroxyethylethylenediaminetriacetate.
[0010] The defoaming agent is one or two of polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether or polyoxypropylene polyoxyethylene glycerol ether.
[0011] The penetrant is one or two of isooctyltriethoxysilane, sodium secondary alkyl sulfate, and sodium α-olefin sulfonate.
[0012] The preparation method of the concrete stabilizer is as follows: N-hydroxymethyl acrylamide, 2-methyl butyl hydroxyethyl polyoxyethylene ether, 2-methyl-1-propylene-1-ol, initiator ammonium persulfate and ferrous sulfate are sequentially added into water and stirred, then the temperature is raised to 50-70°C, substance A (acrylic acid + 2-hydroxy-2-butyl acrylate) is added dropwise, reducing agent stannous chloride is added during the dropping process, substance A is added after reacting for 20-40 minutes, pentanediol is added, the reaction is continued for 0.5-1.5 hours, and spray drying is performed to obtain the concrete stabilizer. The mass ratio of N-hydroxymethyl acrylamide, 2-methyl butyl hydroxyethyl polyoxyethylene ether, 2-methyl-1-propylene-1-ol, acrylic acid, 2-hydroxy-2-butyl acrylate and pentanediol is 10:180-220:22-28:12-15:25-30:32-38.
[0013]
[0014] Preparation method of anti-cracking cement: In order to fully ensure the grading of anti-cracking cement particles and give full play to the role of powder anti-cracking agent, the grinding process adopts a separate grinding method. Cement clinker and desulfurized gypsum are ground together, and mineral powder, fly ash, and concrete powder anti-cracking agent are ground together. After separate grinding, they are mixed and compounded according to proportion to form an anti-cracking cement product.
[0015] The anti-cracking cement can be applied to marine engineering concrete, hydraulic mortar concrete and buildings in corrosive environments of chemical enterprises.
[0016] The technical principle of the present invention is as follows: (1) adopting a separate grinding method to make the particles of the anti-cracking cement reach a continuous gradation; (2) the anti-cracking agent is added to the mineral powder and fly ash and ground together, which can avoid the reduction of the effect of the effective ingredients at high temperature; (3) through the complexing and solubilization effect, more hydrated calcium silicate is formed, and at the same time, the hydration reaction of the mineral powder and fly ash is promoted, and a small amount of chloride ions and sulfate ions can be solidified; (4) nano silica ash and floating beads, as fillers and dispersants for anti-cracking cement, can provide active silicon ions and aluminum ions on the one hand, and can form gel in the capillary pores of concrete on the other hand, reduce the capillary pores, and prevent seawater from entering the concrete for a long time; (5) using a defoaming agent to further reduce the capillary voids, improve the compactness of the concrete, and improve the strength of the concrete; (6) the penetrant can reduce the internal stress of the capillaries in the concrete slurry, so that more gel is formed inside the capillary pores to avoid the cracking of the concrete. (7) Concrete stabilizer in the masterbatch. In terms of performance, the side chains formed by 2-methylbutyl hydroxyethyl polyoxyethylene ether can improve the concrete's popular properties, and the side chains of 2-hydroxy-2-butyl acrylate can inhibit the cracking of concrete. In addition, the polymer structure formed by polymerization can break the silicon-oxygen bond and aluminum-oxygen bond in the cementitious material, releasing freely movable Si and Al ion monomers, forming new silicon-aluminum-oxygen bonds or silicon-aluminum-chloride, and solidifying the chloride ions in seawater.
[0017] The technical effects of the present invention are:
[0018] 1. The preparation method of marine engineering concrete is simplified, and there is no need to add any additional expansion and anti-corrosion admixtures during the concrete production process; the production process of anti-cracking cement is simple, just like the production of ordinary cement, and there is no need to change the process.
[0019] 2. Marine concrete made with anti-cracking cement solves the problem of concrete cracks. On the one hand, it can inhibit the shrinkage cracking of large-volume marine concrete, avoid the generation of cracks, prevent ions from entering the concrete, and reduce the erosion of the internal concrete by ions. On the other hand, anti-cracking cement can solidify the chloride ions in seawater during the hydration process, reduce the degree of erosion on concrete, and at the same time improve the compressive strength and performance of concrete, thereby improving the anti-scouring performance of marine concrete and improving the durability of marine concrete. In addition, the capillary structure of anti-cracking cement in hydrated dense concrete will not pollute the seawater and affect marine life. DETAILED DESCRIPTION
[0020] The effects are described below with reference to embodiments.
[0021] Example 1: Preparation of concrete powder anti-cracking agent
[0022] Formula (weight ratio): 25% nano silica fume + 25% floating beads + 50% masterbatch; wherein, the masterbatch is compounded by 55% concrete stabilizer + 15% complexing agent (diethylenetriaminepentaacetic acid) + 15% defoaming agent (polyoxyethylene polyoxypropylene pentaerythritol ether) + 15% penetrant (isooctyltriethoxysilane).
[0023] Among them, the preparation method of the concrete stabilizer is as follows: 10g of N-hydroxymethyl acrylamide, 200g of 2-methyl butyl hydroxyethyl polyoxyethylene ether, 25g of 2-methyl-1-propylene-1-ol, 5g of initiator ammonium persulfate and 5g of ferrous sulfate solution with a concentration of 0.1% are sequentially added into a stirrer filled with 300g of water and stirred, the temperature is raised to 60°C for 30min, A (13g of acrylic acid + 27g of 2-hydroxy-2-butyl acrylate) is added dropwise, and the dripping is completed in 60min. When the dripping is completed for 30min, 2g of reducing agent stannous chloride is directly added. After the dropwise addition of substance A is completed, 35g of pentanediol is added after the reaction for 30min, and after 1 hour, the concrete stabilizer is obtained by spray drying.
[0024] Example 2: Special anti-cracking cement for marine engineering concrete
[0025] Formula (weight ratio): 76% clinker, 5% desulfurized gypsum, 7% mineral powder, 7% fly ash, 5% concrete powder anti-cracking agent. The physical index of anti-cracking cement refers to PO42.5 cement index, and the residue on 45μm sieve is 6.0±1%.
[0026] Preparation method of anti-cracking cement: In order to fully ensure the grading of anti-cracking cement particles and give full play to the role of powder anti-cracking agent, the grinding process adopts a separate grinding method. Cement clinker and desulfurized gypsum are ground together, and mineral powder, fly ash, and concrete powder anti-cracking agent are ground together. After separate grinding, they are mixed and compounded according to proportion to form an anti-cracking cement product.
[0027] The application of the anti-cracking cement prepared in Example 2 in marine engineering concrete and the comparison test with ordinary cement in marine engineering concrete are shown below.
[0028] The test method reference standards GB175 "Ordinary Portland Cement"; GB / T50082 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete"; GB / T50081 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" and GB / T50080 "Test Methods for Ordinary Concrete Mixtures".
[0029] 1. The physical indicators of the anti-cracking cement and ordinary cement prepared in Example 2 are shown in Table 1.
[0030] Table 1 Physical indexes of anti-cracking cement and ordinary cement
[0031]
[0032] Result analysis: both ordinary cement and anti-cracking cement meet the standard of PO42.5 cement in GB175 "Ordinary Portland Cement". However, the hydration heat of the anti-cracking cement of the present invention is significantly reduced, and the fluidity of the mortar is improved.
[0033] 2. The test indicators of anti-cracking cement in C40 marine engineering concrete are as follows:
[0034] The raw material ratio of ordinary cement and anti-cracking cement used in marine engineering concrete is shown in Table 2, and the test results are shown in Table 3:
[0035] Table 2 Ratio of ordinary cement and anti-cracking cement used in C40 marine engineering concrete (Kg / m 3 )
[0036]
[0037]
[0038] Remark:
[0039] (1) The mineral powder is grade S95, the fly ash is grade II, the fineness modulus of the machine-made sand is 2.6, the particle size of the crushed stone is 5-25 mm, and the solid content of the admixture (polycarboxylic acid admixture, preparation method: 20% polycarboxylic acid water reducer + 2.0% sodium gluconate + 78% water) is 10 + 1%, water reduction rate ≥ 25%;
[0040] (2) Test 2: using anti-cracking cement, the amount of cement was reduced and supplemented with the same amount of machine-made sand and gravel.
[0041] (3) Ordinary marine concrete expansive admixture powder product, the ratio is (weight ratio): magnesium oxide expansive component 55%, powder carboxylic acid dense component 21%, sodium silicate reinforcing component 12%, calcium stearate hydrophobic component 12%; ordinary marine concrete anticorrosive admixture powder product, the ratio is (weight ratio): isobutyl triethoxy silane component 50%, sodium nitrite component 15%, magnesium fluorosilicate component 15% and sodium phosphate component 20%.
[0042] Table 3 Test performance indicators
[0043]
[0044] Result analysis:
[0045] (1) When ordinary cement is used to prepare marine concrete, additional expansion admixtures / anticorrosive admixtures are required to reduce the cracking of concrete and inhibit the corrosion of chloride ions in seawater; when the anti-cracking cement of the present invention is used to prepare marine concrete, no additional admixtures are required;
[0046] (2) In test 1, crack-resistant cement was used in place of ordinary cement. The concrete flowability and strength were significantly better than those of ordinary marine concrete, especially in terms of resistance to seawater scouring. After 1,000 scourings at 2.0 MPa, the depth of crack-resistant cement was 3 mm, which was significantly lower than the 8 mm depth of ordinary marine concrete. In addition, the density of marine concrete was significantly improved after the use of crack-resistant cement, as shown in the electric flux, the reduction of crack area, and the number of freeze-thaw cycles.
[0047] (3) It can be seen from Test 2 that the use of anti-cracking cement can reduce the amount of cement used, and the performance, strength and durability of marine engineering concrete are better than those of marine engineering concrete prepared with ordinary cement and anti-cracking admixtures.
[0048] 3. Application of anti-cracking cement in hydraulic mortar
[0049] The application of anti-cracking cement in hydraulic mortar, the proportion is shown in Table 4, and the mortar performance test is shown in Table 5.
[0050] Table 4 Application of anti-cracking cement in hydraulic mortar Mortar M10 ratio (Kg / m 3 )
[0051]
[0052] Note: Fly ash, machine-made sand, admixtures, expansion admixtures and anti-corrosion admixtures are the same as those in Table 2.
[0053] Table 5 Mortar M10 properties
[0054]
[0055] analyze:
[0056] (1) When ordinary cement is used to prepare hydraulic mortar, additional expansion admixtures and anti-corrosion admixtures are required to reduce the cracking of concrete and improve the compactness of marine concrete; when anti-cracking cement is used to prepare hydraulic mortar, no additional admixtures are required;
[0057] (2) In Test 1, crack-resistant cement was used instead of ordinary cement. The consistency, flowability and strength of the mortar were significantly better than those of ordinary marine concrete, especially in terms of resistance to water scouring. After 1000 scourings at 2.0 MPa, the depth of the crack-resistant cement was 2 mm, which was significantly lower than the 5 mm depth of ordinary hydraulic mortar. In addition, from the perspective of impermeability and bonding properties, the density of the hydraulic mortar was significantly improved after the use of crack-resistant cement.
[0058] Example 3: Preparation of concrete powder anti-cracking agent
[0059] Formula (weight ratio): 25% nano silica fume + 25% floating beads + 50% masterbatch; wherein the masterbatch is compounded by 60% concrete stabilizer + 10% complexing agent (diethylenetriaminepentaacetic acid) + 10% defoamer (polyoxyethylene polyoxypropanolamine ether) + 20% penetrant (sodium secondary alkyl sulfate). The preparation method of the concrete stabilizer is the same as that of Example 1.
[0060] Example 4: Special anti-cracking cement for marine engineering concrete
[0061] Formula (weight ratio): 78% clinker, 4% desulfurized gypsum, 6% mineral powder, 7% fly ash, 5% concrete powder anti-cracking agent. The physical index of anti-cracking cement refers to PO42.5 cement index, and the residue on 45μm sieve is 6.0±1%.
[0062] Preparation method of anti-cracking cement: In order to fully ensure the grading of anti-cracking cement particles and give full play to the role of powder anti-cracking agent, the grinding process adopts a separate grinding method. Cement clinker and desulfurized gypsum are ground together, and mineral powder, fly ash, and concrete powder anti-cracking agent are ground together. After separate grinding, they are mixed and compounded according to proportion to form an anti-cracking cement product.
[0063] Example 5: Preparation of concrete powder anti-cracking agent
[0064] Formula (weight ratio): 25% nano silica fume + 25% floating beads + 50% masterbatch; wherein the masterbatch is compounded by 50% concrete stabilizer + 15% complexing agent (diethylenetriaminepentaacetic acid) + 15% defoamer (polyoxypropylene polyoxyethylene glycerol ether) + 20% penetrant (sodium a-olefin sulfonate). The preparation method of the concrete stabilizer is the same as that of Example 1.
[0065] Example 6: Special anti-cracking cement for marine engineering concrete
[0066] Formula (weight ratio): 74% clinker, 6% desulfurized gypsum, 8% mineral powder, 8% fly ash, 4% concrete powder anti-cracking agent. The physical index of anti-cracking cement refers to PO42.5 cement index, and the residue on 45μm sieve is 6.0±1%.
[0067] Preparation method of anti-cracking cement: In order to fully ensure the grading of anti-cracking cement particles and give full play to the role of powder anti-cracking agent, the grinding process adopts a separate grinding method. Cement clinker and desulfurized gypsum are ground together, and mineral powder, fly ash, and concrete powder anti-cracking agent are ground together. After separate grinding, they are mixed and compounded according to proportion to form an anti-cracking cement product.
Claims
1. A concrete powder anti-cracking agent, characterized in that: The components and weight ratios thereof are: 20-30% of nano silica fume, 20-30% of floating beads, and 40-60% of masterbatch, wherein the components and weight ratios of the masterbatch are: 50-60% of concrete stabilizer, 10-15% of complexing agent, 10-15% of defoaming agent, and 10-20% of penetrant.
2. A concrete powder anti-cracking agent as claimed in claim 1, characterized in that: The preparation method of the concrete stabilizer comprises the following steps: adding N-hydroxymethyl acrylamide, 2-methyl butyl hydroxyethyl polyoxyethylene ether, 2-methyl-1-propylene-1-ol, initiator ammonium persulfate and ferrous sulfate into water in sequence, stirring, then heating to 50-70° C., dropping a substance A compounded with acrylic acid and 2-hydroxy-2-butyl acrylate, adding a reducing agent stannous chloride during the dropping process, adding pentanediol after reacting for 20-40 minutes after the dropping of substance A is completed, continuing the reaction for 0.5-1.5 hours, and spray drying to obtain the concrete stabilizer.
3. A concrete powder anti-cracking agent as claimed in claim 2, characterized in that: The mass ratio of the N-hydroxymethyl acrylamide, 2-methyl butyl hydroxyethyl polyoxyethylene ether, 2-methyl-1-propylene-1-ol, acrylic acid, 2-hydroxy-2-butyl acrylate and pentanediol is 10:180-220:22-28:12-15:25-30:32-38.
4. A concrete powder anti-cracking agent as claimed in claim 1, characterized in that: The complexing agent is one or two of diethylenetriaminepentaacetic acid and trisodium hydroxyethylethylenediaminetriacetate.
5. The concrete powder anti-cracking agent according to claim 1, characterized in that: The defoaming agent is one or two of polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether or polyoxypropylene polyoxyethylene glycerol ether.
6. The concrete powder anti-cracking agent according to claim 1, characterized in that: The penetrant is one or two of isooctyltriethoxysilane, sodium secondary alkyl sulfate, and sodium α-olefin sulfonate.
7. The concrete powder anti-cracking agent according to claim 1, characterized in that: The components and weight ratio thereof are: 25% of nano silica fume, 25% of floating beads and 50% of masterbatch.
8. A special anti-cracking cement for marine engineering concrete, characterized in that: The components and weight ratio thereof are: 73-78% cement clinker, 4-6% desulfurized gypsum, 6-8% mineral powder, 6-8% fly ash, and 4-5% of the concrete powder anti-cracking agent described in any one of claims 1-7.
9. The method for preparing the special anti-cracking cement for marine engineering concrete according to claim 8, characterized in that: The grinding process adopts a separate grinding method. Cement clinker and desulfurized gypsum are ground together, and mineral powder, fly ash, and concrete powder anti-cracking agent are ground together. After separate grinding, they are mixed and compounded according to proportion to form an anti-cracking cement product.
Citation Information
Cited By
Mine filling curing material prepared from household garbage incineration fly ash and preparation method of mine filling curing material
CN120717764A
Mine filling solidified material prepared from domestic waste incineration fly ash and preparation method thereof
CN120717764B